Hspa13 Promotes Plasma Cell Production and Antibody Secretion - He, Youdi; Xu, Ruonan; Zhai, Bing; Fang, Ying; Hou, Chunmei; Xing, Chen; Xiao, He; Chen, Guojiang; Wang, Xiaoqian; Ma, Ning; Han, Gencheng; Wang, Renxi (Frontiers in Immunology, 2020)
Generation of large amounts of plasma cells (PCs) is a main characteristic of systemic lupus erythematosus (SLE) patients. We hypothesize that Hspa13, a member of the heat shock family, plays a critical part in the control of PC differentiation. To test the hypothesis, we used LPS-activated B cells and a newly established mouse line with a CD19cre-mediated B cell-specific deletion of Hspa13 (Hspa13 cKO). We found that Hspa13 mRNA was increased in PCs from drug (atacicept)-treated lupus-prone mice and LPS-stimulated plasmablast (PBs) and PCs. Critically, PBs and PCs but not naïve B cells and germinal center (GC) B cells express high levels of Hspa13. In contrast, the Hspa13 cKO resulted in reduction of BPs, PCs and antibodies induced in vitro by LPS and in vivo by sheep red blood cells (SRCs) or 4-hydroxy-3-nitrophenylacetyl (NP)-immunized mice. Accordingly, the Hspa13 cKO reduced class-switched and somatically hypermutated antibodies with defective affinity maturation. Furthermore, our work showed that Hspa13 interacts with proteins (e.g., Bcap31) in the endoplasmic reticulum (ER) to positively regulate protein transport from the ER to the cytosol. Importantly, Hspa13 mRNA was also increased in B220+ cells from patients with MM or SLE, whereas Hspa13 cKO reduced autoantibodies and proteinuria in pristane-induced lupus and lupus-prone MRL/lpr mouse model. Collectively, our data suggest that Hspa13 is critical for PC development and may be a new target to eliminate pathologic PCs.